(untitled) - Gogola, Marian (Doprava a spoje, 2010)
This paper presents the model analysis of building impact of expressway R1 on transport network of city of Ruzomberok. The traffic problem of this city consists in carrying the external traffic on the inner city transport network and that causes the problem with congestion of inner city traffic. Therefore the modelling approach is needed. This approach is based on the forecasting method which is related to the evaluation of the future status in two cases: if the expressway will be build or will be not build. The results provide the image about the future status which would be critical, if the expressway will be not build.